1997
DOI: 10.1097/00004424-199702000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Temporal Evolution of Acute Spinal Cord Injury

Abstract: Acute spinal cord injury in a rat model is well visualized on pre- and postcontrast MR scans at 1.5 T. Observation of T2 changes and disruption of the blood-spinal cord barrier provide markers for temporal assessment of spinal cord injury in the rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…It is interesting to compare our studies with those of Runge et al (13), who also reported in vivo, longitudinal contrast studies of experimental SCI. Our observation of changes in the lesion length with time is consistent with their results.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…It is interesting to compare our studies with those of Runge et al (13), who also reported in vivo, longitudinal contrast studies of experimental SCI. Our observation of changes in the lesion length with time is consistent with their results.…”
Section: Discussionmentioning
confidence: 56%
“…Our observation of changes in the lesion length with time is consistent with their results. As pointed out in the Introduction, Runge et al (13) reported postcontrast changes at a single time point following Gd administration. In contrast, we concentrated on the dynamic changes in contrast enhancement in order to follow the spatial-temporal evolution of injury for a longer period of time.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations